2021
DOI: 10.1080/2162402x.2021.1933332
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel gene signature to predict prognosis and response to PD-1 blockade in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common kidney malignancy characterized by a poor prognosis. The treatment efficacy of immune checkpoint inhibitors (ICIs) also varies widely in advanced ccRCC. We aim to construct a robust gene signature to improve the prognostic discrimination and prediction of ICIs for ccRCC patients. In this study, adopting differentially expressed genes from seven ccRCC datasets in GEO (Gene Expression Omnibus), a novel signature (FOXM1&TOP2A) was constructed in TCGA (The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Recent studies have shown that cell cycle-related genes are strongly associated with the prognosis of many malignant tumors. It is possible to evaluate tumor immunogenicity and response to ICIs therapy by analyzing cell cycle-related genes 47 . In this study, two genes (ANGPTL4 and PLK1) of the IGSPP that we constructed were involved in the regulation of the tumor cell cycle 36 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cell cycle-related genes are strongly associated with the prognosis of many malignant tumors. It is possible to evaluate tumor immunogenicity and response to ICIs therapy by analyzing cell cycle-related genes 47 . In this study, two genes (ANGPTL4 and PLK1) of the IGSPP that we constructed were involved in the regulation of the tumor cell cycle 36 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Different metabolism signatures may cause prognosis heterogeneity in ccRCCs, suggesting the possibility to classify ccRCCs from metabolic perspective. To date, variable immune-related classification methods based on gene signatures or immune components in transcriptome studies showed prediction values in ccRCC immunotherapy ( 18 20 ). However, the interplay of immune activity with metabolism is crucial for the regulation of the TME network.…”
Section: Introductionmentioning
confidence: 99%
“…( 52 ), Yin et al. ( 53 ), and Zhang Z et al. ( 54 ) constructed gene signatures according to differential expression genes between tumor and normal tissues; Zhang et al.…”
Section: Discussionmentioning
confidence: 99%